Magnetic circular dichroism within the algebraic diagrammatic construction scheme of the polarization propagator up to third order - Fedotov, Daniil A.; Scott, Mikael; Scheurer, Maximilian; Rehn, Dirk R.; Dreuw, Andreas; Coriani, Sonia (The journal of chemical physics, 2022)
We present an implementation of the B term of Magnetic Circular Dichroism (MCD) within the Algebraic Diagrammatic Construction (ADC) scheme of the polarization propagator and its Intermediate State Representation. As illustrative results, the MCD spectra of the ADC variants ADC(2), ADC(2)-x, and ADC(3) of the molecular systems uracil, 2-thiouracil, 4-thiouracil, purine, hypoxanthine 1,4-naphthoquinone, 9,10-anthraquinone, and 1-naphthylamine are computed and compared with results obtained by using the Resolution-of-Identity Coupled-Cluster Singles and Approximate Doubles method, with literature Time-Dependent Density Functional Theory results, and with available experimental data.